The Impact of Carbonated Beverage Packaging on Consumer Psychology: The Impact of Carbonated Beverage Packaging on Consumer Psychology - KM Safin Ahmed; Dhruba Sarker; Farhan Ahmed (Jurnal Aplikasi Manajemen, Ekonomi dan Bisnis, 2023)
This study looks at what clients' insights and expectations for buys are meant for by the bundling of carbonated refreshments and how this affects their choices to purchase an item. The objective of this study is to distinguish the elements that add to the progress of refreshment bundling. The study's focus is on Bangladeshi, primarily young members of Generation Z. The aesthetic impact of the container design, as well as the beverage's flavor characteristics and brand perception, influence consumers' choices for bottled beverages. How to create appealing beverage packaging that takes into account the emotional needs of consumers is one of the most important aspects of increasing beverage sales. When designing a new container that meets the emotional expectations of consumers, the study's findings can offer valuable guidance to bottlers and designers. Packaging plays a significant role in consumers' purchasing decisions and can even serve as a "silent salesperson" by promoting a particular brand, so producers of carbonated beverages should pay close attention to it.